PFKFB3-dependent redox homeostasis and DNA repair support cell survival under EGFR-TKIs in non-small cell lung carcinoma - Nadiia Lypova; Susan M. Dougherty; Brian F. Clem; Jing Feng; Xinmin Yin; Xiang Zhang; Xiaohong Li; Jason A. Chesney; Yoannis Imbert-Fernandez (Cancer & Metabolism)
Abstract Background The efficacy of tyrosine kinase inhibitors (TKIs) targeting the EGFR is limited due to the persistence of drug-tolerant cell populations, leading to therapy resistance. Non-genetic mechanisms, such as metabolic rewiring, play a significant role in driving lung cancer cells into the drug-tolerant state, allowing them to persist under continuous drug treatment. Methods Our study employed a comprehensive approach to examine the impact of the glycolytic regulator 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB3) on the adaptivity of lung cancer cells to EGFR TKI therapies. We conducted metabolomics to trace glucose rerouting in response to PFKFB3 inhibition during TKI treatment. Live cell imaging and DCFDA oxidation were used to quantify levels of oxidation stress. Immunocytochemistry and Neutral Comet assay were employed to evaluate DNA integrity in response to therapy-driven oxidative stress. Results Our metabolic profiling revealed that PFKFB3 inhibition significantly alters the metabolic profile of TKI-treated cells. It limited glucose utilization in the polyol pathway, glycolysis, and TCA cycle, leading to a depletion of ATP levels. Furthermore, pharmacological inhibition of PFKFB3 overcome TKI-driven redox capacity by diminishing the expression of glutathione peroxidase 4 (GPX4), thereby exacerbating oxidative stress. Our study also unveiled a novel role of PFKFB3 in DNA oxidation and damage by controlling the expression of DNA-glycosylases involved in base excision repair. Consequently, PFKFB3 inhibition improved the cytotoxicity of EGFR-TKIs by facilitating ROS-dependent cell death. Conclusions Our results suggest that PFKFB3 inhibition reduces glucose utilization and DNA damage repair, limiting the adaptivity of the cells to therapy-driven oxidative stress and DNA integrity insults. Inhibiting PFKFB3 can be an effective strategy to eradicate cancer cells surviving under EGFR TKI therapy before they enter the drug-resistant state. These findings may have potential implications in the development of new therapies for drug-resistant cancer treatment.